Website-Based Module Design on Virus Materials for Class X High School - Zikra; Yanti, Febri; Elna Amatul, Friska (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
This study aims to produce a website-based module on Virus material for class X high school students. This research was conducted at PGRI University, West Sumatra, in the 2022/2023 academic year. The method used in this research is ADDIE, where the stages of this ADDIE consist of analysis, design, development, implementation, and evaluation. However, considering the limited time in this research process, the researchers conducted research only up to the design stage. The instrument used in data collection used a student analysis questionnaire. Data analysis techniques in this study are descriptive data and qualitative data. Based on the results of the analysis of the teaching materials used in the learning process in the form of high school biology textbooks, it shows that the books analyzed still have several shortcomings that do not describe one of the core competencies and basic competencies. Based on the results of the analysis of students, it was found that students still have difficulty in understanding biology learning resources, especially on virus material because the material is abstract and cannot be observed directly, besides that there are many terms that are not understood by students, and the most The main reason is the lack of availability of good learning resources. Thus, it is necessary to develop modules so that students better understand virus learning.